Evolution of Generalized Trust – The Global Evidence over 41 Years - Felix Roth (University of Hamburg, Department of Economics, Senior Lecturer in International Economics, 2025)
By constructing a unique international database on generalized trust covering 142 countries worldwide for the 41 years from 1980 to 2020, this paper finds a pronounced intertemporal variation of generalized trust over time in a majority of countries across the globe. 3 When analyzing the time series patterns over the last two decades, a significant divergence in generalized trust between OECD and non-OECD economies is found. While the OECD economies saw an increase in generalized trust, the non-OECD economies faced a pronounced decline. In particular, North-Western European and Liberal Market economies drive the increase in trust in OECD economies. In particular, Asian and African economies drive the decline in non-OECD economies. Those countries' decline is responsible for a global decline in trust.
Keywords: C23; O47; O50; Z13; 330; Generalized Trust; Intertemporal Variation; Stability; Panel Data; Endogeneit